ANALISIS PERHITUNGAN TEBAL LAPIS TAMBAHAN PADA JALAN PANGERAN SURYANATA – PATUNG LEMBUSWANA KOTA SAMARINDA - NI, DA (KURVA S JURNAL MAHASISWA, 2014)
Technical planning of the program carried out in East Kalimantan province are still using Component Analysis Method ISO 1732-1989-F with manual calculation. Along with the development of technology, Technical Directorate of the Directorate General of Highways, Ministry of Public Works introduced a new method using software such as Flexible Pavement Design Software (SDPJL) in 2011. The purpose of this study was to compare the additional overlay on flexible pavement using Component Analysis Method ISO 1732-1989-F and Flexible Pavement Design Software (SDPJL). Location of the study was conducted on roads Santan-Bontang in East Kalimantan province. Primary data used is the Land Capability (CBR value), Road Condition Index (RCI), and the geometric path which was held on 14 and 15 February 2013. Secondary data traffic Daily Average (LHR), Deflection (Benkelman beam), climate and temperature data obtained from the Planning and Monitoring Unit of National Roads (P2JN) East Kalimantan. From these data, overlay is calculated using Component Analysis Method SNI 1732-1989-F and Flexible Pavement Design Software (SDPJL). Overlay of additional analysis calculations using the obtained thick Component Analysis Method AC-WC 4 cm and AC-BC 2.35 cm, while the overlay of additional calculations using the method of Flexible Pavement Design Software (SDPJL) obtained thick AC-WC 4 cm and AC-BC 13 cm. Differences the calculation caused of parameters the data used.